2020
DOI: 10.1136/bmjopen-2020-043487
|View full text |Cite
|
Sign up to set email alerts
|

Predicting dementia diagnosis from cognitive footprints in electronic health records: a case–control study protocol

Abstract: IntroductionDementia is a group of disabling disorders that can be devastating for persons living with it and for their families. Data-informed decision-making strategies to identify individuals at high risk of dementia are essential to facilitate large-scale prevention and early intervention. This population-based case–control study aims to develop and validate a clinical algorithm for predicting dementia diagnosis, based on the cognitive footprint in personal and medical history.Methods and analysisWe will u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…It has been reported that more than 10% of community-dwelling subjects older than 70 years suffer from very mild or mild dementia [ 22 ]. Data-informed decision-making strategies to identify individuals at high risk of dementia could be essential to facilitating large-scale prevention and early intervention [ 25 ]. Triage tests such as the MMSE are used in clinical practice to rapidly assess the cognitive condition [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that more than 10% of community-dwelling subjects older than 70 years suffer from very mild or mild dementia [ 22 ]. Data-informed decision-making strategies to identify individuals at high risk of dementia could be essential to facilitating large-scale prevention and early intervention [ 25 ]. Triage tests such as the MMSE are used in clinical practice to rapidly assess the cognitive condition [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, the incidence of AD has been reported to be higher in those individuals with lower education (16). Previous studies showed that digital health data, cognitive performance such as memory, and neuropsychiatric symptoms can help identify those with dementia from normal subjects (17)(18)(19)(20)(21). Some research groups (19) have suggested that a diagnosis of dementia can be made from health recording data.…”
Section: Discussionmentioning
confidence: 99%
“…According to the cognitive footprint theory, age at exposures was classified into three age periods: earlier (21–45 years), mid (45–64), and late-life (≥65) as specified in the protocol published earlier. 17 Only mid and late life were considered in this study since the observation period before the dementia diagnosis was shorter than 20 years. All factors were broken down into mid and late-life factors, based on the exposure period, except education.…”
Section: Methodsmentioning
confidence: 99%